Intraluminal Diverticular Duodenal Duplication With Recurrent Abdominal Pain: A Case Report - Chen, Jie; Xiong, Guo-zuo; Tan, Xiong; Wu, Fei; Luo, Dong-yang; Zou, Qing-qing; Deng, Zhihe; Bi, Guo-shan (Frontiers in Pediatrics, 2022)
Duodenal duplication is a rare congenital anomaly and may manifest as pancreatitis, gastrointestinal bleeding, abdominal pain, perforation, and obstruction. Here, we present a case of intraluminal diverticular duodenal duplication (IDDD) in a child with recurrent abdominal pain caused by a large hole-like structure in the duodenal bulb. This condition has rarely been reported. An 11-year-old boy presented with recurrent attacks of abdominal pain. Upper endoscopy examination and barium swallowing led to an initial diagnosis of IDDD; this diagnosis was confirmed by operative findings and histopathological signs. He underwent a subtotal excision and duodenal anastomosis. No serious complications occurred following treatment. The patient was followed up for 8 months, and his condition improved without symptoms.